Exploring morphovariations in bael (Aegle marmelos) (Current Horticulture, 2024)
Bael (Aegle marmelos Correa), an indigenous tree having wide genetic diversity, is found growing in different parts except at high altitude and in cold region of the country. Most of the woody plants produce flowers and fruits on new growth or on young leafy shoots, but a few plants bear fruits on main stems, primary and secondary woody branches. This phenomenon is known as cauliflory. Such flowering and fruiting are also observed in bael germplasm established at field gene bank at CHES, Godhra. It has been noticed that bael produce flowering and fruiting on main stems and primary, secondary, tertiary, fourth and fifth branches, and even on previous and current season's growth of shoots. Simultaneously, it has also been also observed that fruits may appear on first, second, third, fourth, fifth, sixth, seventh and eighth year growing woody stems of bael tree under semi-arid conditions in western India. Therefore, bael is a culiflorous and ramiflorus tree, such type of flowering and fruiting are found in bael, but it is common in bael variety, Goma Yashi and NB-16. Vivipary is of unusual occurrence in bael. Generally, such fruits are not good in taste. If cut exposed, germinated seeds inside the fruits are visible very clearly. High humidity and warm weathers appear to be associated with viviparous fruits in bael. The pollen-grains of bael are found to exert a direct effect on size, shape and styler end cavity of fruits, seeds and speed of development of fruits and on time of ripening of fruits of asexually propagated bael plant. Such effect on fruits may be due to metaxenia effect in bael. Variations in number of petals and sepals, number of leaflets and thorns are also observed.
Keywords: Morphovariations; Culiflory; Flowering; Metaxenia; Vivipary; Ramiflorus